Oil in freshwater : chemistry, biology, countermeasure technology : proceedings of the Symposium of Oil Pollution in Freshwater, Edmonton, Alberta, Canada - Vandermeulen, J. H.; Hrudey, S. E. (Steve E.) (Pergamon Press, 1987)
Oil in Freshwater: Chemistry, Biology, Countermeasure Technology.